Tridimenzionalna analiza gibanja hrbtenice in zaznavanje položaja sklepov vratne hrbtenice pri zdravih preiskovancih - Jamnik, Helena (Rehabilitacija (Ljubljana), 2013)
Objectives: Healthy volunteers' active range of motion in cervical and lumbar segments of spine in all standard planes of motion was measured using the Zebris CMS20 device, and interexaminer reliability of these measurements was assessed. We also evaluated the inter-examiner reliability of cervical joint position sense measurements using the test of head turning into neutral position. Methods: A total of 28 healthy participants were included. Two examiners performed the measurements of three-dimensional spinal motions and the test for cervical joint position sense. Descriptive statistics were calculated for active cervical and lumbar range of motion and relocation position error for cervical joint position sense. Mean coefficient of variation was calculated for all movements of cervical and lumbar range of motion. Correlations between all the measurements and age were estimated. Test-retest reliability was assessed using intra-class correlation coefficient (ICC). Results: The results for active cervical range of motion were comparable with the data published in the literature. Active cervical and lumbar ROM decreased with increasing age. Inter-examiner reliability of measurement of active cervical and lumbar range of motion was very high. Test-retest reliability of measurement of cervical joint position sense using the test of head turning in neutral position was poor. Conclusion: We defined normative values and confirmed inter-examiner reliability for measuring active cervical and lumbar range of motion using a system for three-dimensional analyses of spinal motion. The reliability of cervical joint position sense assessment using the protocol of head turning in neutral position was not proven.
Keywords: gibanje; gibljivost hrbtenice; healthy subjects; hrbtenica; ponovljivost; reproducibility; spinal mobility; spine motion; zdravi preiskovanci